Strengthening child inclusion in the classroom in rural schools of Pakistan and Afghanistan: What did we learn by testing the system dynamics protocol for community engagement?. (March 2019) - Trani, Jean-François; Bakhshi, Parul; Mozaffari, Alan; Sohail, Munib; Rawab, Hashim; Kaplan, Ian; Ballard, Ellis; Hovmand, Peter
Access to education has been the central tenet of the Millennium Development Goal 2, which focused strongly on increasing enrolment yet failed to promote education quality and equity and address contextual complexities that sustain exclusion. As a consequence, many children are not learning. There is growing recognition that effective, efficient and equitable education for all will not be achieved without better accountability. The present paper details innovative methods for strengthening the learning process through better social accountability. The paper defines and tests in rural schools of Afghanistan and Pakistan a community-based system dynamics protocol using participatory group model building (GMB) techniques. We tested the protocol with two groups of teachers and one group of children, with the three produced causal loop diagrams highlighting factors that influence learning in the classroom from the perspectives of the participants. The sessions showed interest, engagement, quick mastery of how GMB methods work and clear understanding of how the current classroom system hinders learning for many students. Researchers found that large autonomy and initiative could be left to the workshop participants, keeping the facilitator's role to one of explaining the method and asking clarification about causal relations.